Solubility of Dihydroxylammonium 5, 5′-Bistetrazole-1, 1′-diolate in (formic acid, water) and their binary solvents from 298.15 K to 333.15 K at 101.1 kPa. (January 2019) - Li, Dan; Cao, Duan-Lin; Chen, Li-Zhen; Wang, Jian-Long; Jiang, Zhen-Ming; Ma, Xiao
Highlights: Solubility of TKX-50 in (formic acid, water) and their binary solvents were measured. The mole fraction solubility of TKX-50 were correlated with several models. It will provide support for further research of crystallization and spheroidization. Abstract: In this study, the solubility of Dihydroxylammonium 5, 5′-Bistetrazole-1, 1′-diolate (TKX-50) in formic acid, water and mixed solvents (formic acid + water) were measured with the temperature ranging from 298.15 K to 333.15 K by using a laser dynamic monitoring technique at 101.1 kPa. The experimental data showed that the solubility of TKX-50 increase with the increasing temperature in all solvents and decrease with the decreasing proportion of formic acid in mixed solvents (formic acid + water) at constant temperature. The mole fraction solubility of TKX-50 in pure formic acid and pure water were correlated with the modified Apelblat equation and the van't Hoff equation, the mole fraction solubility in mixed solvents (formic acid + water) were correlated with the (CNIBS)/R-K equation, the Jouyban-Acree model, the Apelblat-Jouyban-Acree model, the van't Hoff-Jouyban-Acree model, the Sun model and the Ma model. The result showed that calculated values correlated by these models are consistent with the experimental data. The solubility of TKX-50 in mixed solvents (formic acid + water) will provide essential support for the further research of crystallization and spheroidization of TKX-50.